Breast tumor IGF1R regulates cell adhesion and metastasis: alignment of mouse single cell and human breast cancer transcriptomics - Obr, Alison E.; Bulatowicz, Joseph J.; Chang, Yun-Juan; Ciliento, Virginia; Lemenze, Alexander; Maingrette, Krystopher; Shang, Quan; Gallagher, Emily J.; LeRoith, Derek; Wood, Teresa L. (Frontiers in Oncology, 2022)
The acquisition of a metastatic phenotype is the critical event that determines patient survival from breast cancer. Several receptor tyrosine kinases have functions both in promoting and inhibiting metastasis in breast tumors. Although the insulin-like growth factor 1 receptor (IGF1R) has been considered a target for inhibition in breast cancer, low levels of IGF1R expression are associated with worse overall patient survival. To determine how reduced IGF1R impacts tumor phenotype, we used weighted correlation gene network analysis (WCGNA) of METABRIC patient data and identified gene modules specific to cell cycle, adhesion, and immune cell signaling inversely correlated with IGF1R expression in human breast cancers. Integration of human patient data with data from mouse tumors revealed similar pathways necessary for promoting metastasis in basal-like mammary tumors with reduced signaling or expression of IGF1R. Functional analyses revealed the basis for the enhanced metastatic phenotype including alterations in E- and P-cadherins.